POLA SEBARAN KARANG LUNAK (Soft Coral) TERHADAP KEDALAMAN YANG BERBEDA DI PANTAI TURUN ABAN, TANJUNG PESONA DAN REBO - Ilham Akbar; Wahyu Adi; Umroh Umroh (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2016)
Soft corals are often spread at a depth below the lowest tide to avoid the drying process. Given the importance Soft Coral existence that so need to do research on the effect of depth to the density of soft corals. The purpose of research comparing the effect of depth to the density of soft corals and that knowing soft coral genus found in ocean Turun Aban, Tanjung Pesona and Karang Kering. This research was conducted in September 2015. The research method used is purposive sampling method for the determination of the station and belt transects for data retrieval soft coral. The research found 6 genus soft coral research site consists of genus Sinularia, Lobophytum, Sarcophyton, rumphella, nephthea and dendronephthya. The genus is found only in the depth of 3 meters and not be found at a depth of 1 meter because soft coral grow at a depth lowest tide line, to avoid the drought. The distribution pattern of soft coral site in the research had clumped pattern distribution